THE DETERMINAT OF FEMALE WORKER’S INCOME IN CENTRAL JAVA - Huruta, Andrian Dolfriandra; Sasongko, Gatot; Arum Sari, Putri Indah (EP FEB UNS, 2019)
This study aims to determine the factors influencing the female workers’ income in Central Java such as age, level of education, number of family dependents, marital status, business field, and type of area. The data used in the study was a secondary data from the Central Bureau of Statistics (National Socio-Economic Survey). The data from the survey were in the form of Household Main Information and Household Members in Central Java in 2008. Methodically, this study used a cross-sectional model with multiple linear regression analysis. The results showed that the variables of age and level of education had a positive and significant influence on the income of female workers, and further, business field had a negative and significant influence on the income of female workers, but the number of family dependents, marital status, and type of area had no significant effect on the income of female workers in Central Java. It implies that the government in Central Java should extend the retirement age of the workforce (especially women), more proactive education in informal education for workers who are still low educated, and the need for integrity of agricultural land which is a source of living for the farmers, a better profit sharing system between the owner of the land and workers, and the right distribution of fertilizers.